Impact of age on risk of recurrence of DCIS: Outcomes of 2996 women treated with breast-conserving surgery over 30 years - Cronin, Patricia A. (Ann Surg Oncol, 2016)
BACKGROUND: Age is a known risk factor for recurrence for women with DCIS treated with breast-conserving surgery (BCS); we explored the relationship between age, other risk factors, and recurrence. METHODS: Using a prospectively maintained database of DCIS patients undergoing BCS from 1978–2010, the association of age and recurrence risk was analyzed using Kaplan–Meier estimates, multivariable analysis (MVA), and competing-risk MVA (CRMVA). RESULTS: 2996 cases were identified. Median follow-up for those without recurrence was 75 mos; 732 had ≥10y follow-up. 363 (12%) had recurrence: 192 (53%) DCIS, 160 (44%) invasive, 11 (3%) unknown. Risk of recurrence decreased with age, even after adjustment for eight clinicopathologic variables on MVA (hazard ratios [HR] with <40y as reference: 40–49y[0.82, p=0.36], 50–59y[0.46, p=0.0005], 60–69y[0.50, p=0.003], 70–79y[0.56, p=0.02], ≥80y [0.21, p=0.0015]). This association persisted for cohorts with and without RT. Using CRMVA, the effect of age on invasive recurrence was empirically stronger than for DCIS recurrence. 10y invasive recurrence was 16% vs. 6.5% in women <40y vs. women ≥40y. Only 0.6% of the population ultimately developed distant disease; those <40y constituted 4.7% (141/2996) of the population but 21% (4/19) of those developing distant disease. CONCLUSIONS: Risk of recurrence of DCIS decreases with age; this effect is particularly strong at the extremes of age, and is independent of other clinicopathologic factors. The oldest women are at low risk of recurrence; the youngest have a higher overall and especially invasive recurrence rate, although mortality remains low. These findings should be incorporated into risk/benefit discussions of treatment options.